HISTOLOGICAL CHANGES IN MALE ACCESSORY REPRODUCTIVE ORGANS IN RATS EXPOSED TO CIGARETTE SMOKE AND THE PROTECTIVE EFFECT OF HONEY SUPPLEMENTATION - Mohamed, Mahaneem; Sulaiman, Siti Amrah; Jaafar, Hasnan (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The effect of cigarette smoke (CS) on histology of male accessory reproductive organs and the possible protective effect of honey supplementation in rats were investigated in this study. Rats received distilled water, honey, CS exposure or honey plus CS exposure. Honey (1.2 g/kg body weight/day) was administered by gavage and CS exposure (3 times per day) was done in a chamber for 13 weeks. CS exposure significantly increased relative weight of epididymis and ventral prostate. There were also significantly increased number of clear cells and epithelial height of cauda epididymis as well as severe interstitial oedema and decreased epithelial height of prostate gland. However, with the supplementation of honey, these histological changes were significantly reversed suggesting the protective effect of honey against the toxic effect of CS on male accessory reproductive organs in rats.